Evaluation of esophagogastric junction relaxation by 4‐second Integrated Relaxation Pressure in achalasia using High Resolution Manometry with water‐perfused catheters. Issue 11 (14th August 2014) - Ortiz, V.; Poppele, G.; Alonso, N.; Castellano, C.; Garrigues, V.
Abstract Background Relaxation of the esophagogastric junction (EGJ) is now evaluated calculating 4‐second integrated relaxation pressure (4‐s IRP) by high resolution manometry (HREPT). Solid‐state catheters have been used to define abnormal values. Our aim was to evaluate 4‐s IRP in esophageal achalasia using HREPT with perfused catheters. Methods From June 2009 to June 2013, 936 HREPT studies have been performed in our unit. Of these, 194 patients having treated achalasia were excluded. Control group was constituted by 695 patients without achalasia, and 47 patients with untreated achalasia constituted the study group. HREPT was performed with water‐perfused catheters. To establish the cut‐off value for 4‐s IRP that better discriminate patients with achalasia from all other patients, a receiver operating characteristic (ROC) analysis was performed. Key Results Twenty three of 47 achalasia patients (49%) showed a 4‐s IRP under 15 mmHg; and seven (15%) had a value under modified Chicago criteria. A cut‐off value for 4‐s IRP of 6.5 mmHg, calculated by ROC analysis, highly discriminates achalasia from the rest of the patients and especially from scleroderma patients (area under the curve: 0.997, 95% CI: 0.995–1.000; p < 0.001). Conclusions & Inferences Cut‐off values for 4‐s IRP defined using HREPT with solid‐state catheters are not adequate for diagnosing esophageal achalasia with water‐perfused systems. A lower value, i.e., 6.5 mmHg, is suggested for this equipment. The diagnostic criteria of esophageal achalasia should be modified for HREPT performed with water‐perfused systems.